2010
DOI: 10.1038/jp.2010.59
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal or postnatal indomethacin exposure and neonatal gut injury associated with isolated intestinal perforation and necrotizing enterocolitis

Abstract: Objective: To examine the role of indomethacin in neonatal gut injury.Study Design: Infants born at gestational age X23 weeks and with birth weights 400-1200 g were included in this prospective prevalence study of neonatal gut injury. Infants with isolated intestinal perforation (IIP) confirmed at laparotomy or at autopsy or with necrotizing enterocolitis (NEC) were identified. Data were abstracted bi-weekly.Result: Among 992 study infants, 58 infants exposed solely to prenatal indomethacin did not show an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 50 publications
(74 reference statements)
0
35
1
Order By: Relevance
“…Awareness of the association of postnatal indomethacin and NEC and the debate regarding the need for treatment of PDA has led to decreased use of postnatal indomethacin in our institution and may account for the observed lack of association with NEC in our study. In the literature, there are conflicting reports, with increased, 4,5 decreased, 62 and unchanged [63][64][65] incidence of NEC being reported after postnatal indomethacin. Although an increased risk for NEC has been reported in black preterm infants, males, and after maternal cocaine use, we did not observe these associations.…”
Section: Discussionmentioning
confidence: 90%
“…Awareness of the association of postnatal indomethacin and NEC and the debate regarding the need for treatment of PDA has led to decreased use of postnatal indomethacin in our institution and may account for the observed lack of association with NEC in our study. In the literature, there are conflicting reports, with increased, 4,5 decreased, 62 and unchanged [63][64][65] incidence of NEC being reported after postnatal indomethacin. Although an increased risk for NEC has been reported in black preterm infants, males, and after maternal cocaine use, we did not observe these associations.…”
Section: Discussionmentioning
confidence: 90%
“…Similar to several reports in the literature, we were also able to demonstrate previously reported associations of focal/SIP with lower gestational age, 1,4-6 lower birth weight, 1,4,5 younger postnatal age, 1,4-6 exposure to indomethacin, 1,2,6,7 exposure to postnatal steroids, 1,7,8,22 hypotension requiring inotropes 4 in the first week after birth and staphylococcal 3,9,13 and Candidial sepsis. 3,9 As far as indomethacin is concerned, early use 23 or use to prevent intraventricular hemorrhage has been shown to be associated with focal SIP in some studies 15,24 but not in others. 12 Sharma et al 24 reported that therapeutic indomethacin had a protective effect on NEC, whereas Wadhwan et al 12 reported that it was associated with focal/SIP.…”
Section: Discussionmentioning
confidence: 98%
“…3,9 As far as indomethacin is concerned, early use 23 or use to prevent intraventricular hemorrhage has been shown to be associated with focal SIP in some studies 15,24 but not in others. 12 Sharma et al 24 reported that therapeutic indomethacin had a protective effect on NEC, whereas Wadhwan et al 12 reported that it was associated with focal/SIP. We did not identify any difference in therapeutic indomethacin use between those who had focal/SIP vs those who had NEC-related perforation.…”
Section: Discussionmentioning
confidence: 98%
“…Pediatrics 2014;134:e1369-e1377 Prophylactic indomethacin during the first 3 days after birth in extremely low birth weight (ELBW) infants (birth weight #1000 g) decreases the incidence of severe intraventricular hemorrhage and patent ductus arteriosus (PDA). 1,2,3 However, administration of indomethacin soon after birth in preterm infants may be associated with an increased risk for spontaneous intestinal perforation (SIP) [4][5][6][7][8] or necrotizing enterocolitis (NEC) with intestinal perforation. 10 The incidence of SIP in ELBW infants is 6%.…”
Section: Discussionmentioning
confidence: 99%
“…27 A meta-analysis showed that antenatal corticosteroids are not associated with SIP. 6 A case-control study of 2105 infants identified the following risk factors for SIP: being outborn from a tertiary level NICU (mother less likely to have received antenatal corticosteroids), treatment with…”
Section: Discussionmentioning
confidence: 99%